Análisis de la evolución de los tributos en las microempresas y su impacto tributario y financiero - Zúñiga Potes, María Lorena (2024)
The present graduation thesis entitled "Analysis of the evolution of taxes in microenterprises and their tax and financial impact" addresses research focused on understanding the evolution of taxes in the financial situation of microenterprises. The objectives include a review of theoretical foundations supporting the entire tax evolution and fiscal collection in this area, as well as the diagnosis of the current situation in microenterprises regarding taxes and the preparation of a technical report presenting results obtained in terms of the tax and financial situation of such companies. On the other hand, the subject in question is based on examining the evolution of taxes specifically in the context of microenterprises, as well as understanding the resulting financial and tax impact. This approach involves evaluating how changes in the structure directly affect organizations, from a fiscal as well as financial standpoint. The analysis aims to provide a comprehensive view of tax dynamics and their impact on the economic stability of microenterprises.